1996
DOI: 10.1088/0963-0252/5/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Discharge equilibrium of a helicon plasma

Abstract: The axial dependence of the plasma density, electron temperature, plasma potentials, and the 488 nm argon ion emission intensity have been measured in argon helicon discharges excited by both right helical and Nagoya III antennas for various magnitudes and directions of the magnetic field B. The plasma parameters were monitored with RF-compensated probes, while the emission line was detected with an optical emission spectrometer that incorporates an optical fibre and a miniature lens. The right helical antenna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
108
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 20 publications
14
108
0
Order By: Relevance
“…Because of the higher threshold for direct excitation from Ar I, one would expect this process to be negligible. Indeed, in a previous paper Sudit and Chen [18] showed that data on the axial variation of 488 nm light agreed with calculations, based on measured T e values, assuming the n 2 dependence of the Ar II process but not with the n dependence of the Ar I process. Thus, the light intensity in our CCD images should be proportional to n 2 σ ν .…”
Section: Interpretation Of Resultsmentioning
confidence: 65%
“…Because of the higher threshold for direct excitation from Ar I, one would expect this process to be negligible. Indeed, in a previous paper Sudit and Chen [18] showed that data on the axial variation of 488 nm light agreed with calculations, based on measured T e values, assuming the n 2 dependence of the Ar II process but not with the n dependence of the Ar I process. Thus, the light intensity in our CCD images should be proportional to n 2 σ ν .…”
Section: Interpretation Of Resultsmentioning
confidence: 65%
“…Recent experimental observations 5,[21][22][23] show that the plasma density for helicon plasma sources often peaks several wavelengths downstream from the antenna, and its axial variation can substantially affect the electromagnetic wave field profiles and power absorption of the plasma electrons. It is, therefore, necessary to develop a two-dimensional (r,z) model to account for the effects of the axial variation of the plasma density, temperature, and applied magnetic field on helicon wave propagation and absorption.…”
Section: Introduction To the Two-dimensional "Rz… Simulation Codementioning
confidence: 99%
“…A mode transition is also observed in helicon plasma sources, which show a three-step mode transition, that is from E mode to H mode and finally to helicon mode. 5 Smullin et al 6 recognized that when the phase velocity of an electromagnetic wave in a rectangular metallic wave guide filled with plasma with constant B field satisfies v ph (ϭ /k)Ӷc, the wave can be treated by the electrostatic approximation. The existence of this mode was observed independently by Trivelpiece and Gould.…”
Section: Introductionmentioning
confidence: 99%